Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3171/2020.6.jns192775
|View full text |Cite
|
Sign up to set email alerts
|

The role of indocyanine green fluorescence in endoscopic endonasal skull base surgery and its imaging correlations

Abstract: OBJECTIVEThe use of endoscope-integrated indocyanine green (E-ICG) has recently been introduced in skull base surgery. The quantitative correlation between E-ICG and T1-weighted gadolinium-enhanced (T1WGd) images for skull base tumors has not been previously assessed, to the authors’ knowledge. In this study, the authors investigated the indications for use and the limitations of E-ICG and sought to correlate the endoscopic fluorescence pattern with MRI contrast enhancement.METHODSFollowing IRB approval, 20 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…More recently, Shahein et al tried to define indications and limitations for the use of ICG based on previous experience and their own experiences with 10 PA cases. In particular, they were the first to systematically correlate MRI images with intraoperative ICG fluorescence, postulating that the various patterns of enhancement seen in MRI are due to the differences between the vascular features of the gland and the tumor [ 22 ]. Starting from these assumptions, they indicated that both the presentation to the sellar surface, the presence of an intact pseudocapsule, and intratumoral bleeding were the main factors that should be considered when selecting cases.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Shahein et al tried to define indications and limitations for the use of ICG based on previous experience and their own experiences with 10 PA cases. In particular, they were the first to systematically correlate MRI images with intraoperative ICG fluorescence, postulating that the various patterns of enhancement seen in MRI are due to the differences between the vascular features of the gland and the tumor [ 22 ]. Starting from these assumptions, they indicated that both the presentation to the sellar surface, the presence of an intact pseudocapsule, and intratumoral bleeding were the main factors that should be considered when selecting cases.…”
Section: Resultsmentioning
confidence: 99%
“…18 In skull base reconstruction, ICG angiography has been employed in several highvolume centers for the same purposes. [19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%